Rencontres radicales : pour des dialogues féministes décoloniaux - Altamimi, Manal; Dor, Tal; Guénif Souilamas, Nacira (Cambourakis, 2018)
Comment tenter de trans/former la conscience de personnes engagées dans des situations de conflit, des tensions sociales et raciales et en quête de changements politiques significatifs ? Trois types de textes se font ici écho : six auteur·e·s analysent les « rencontres radicales » organisées entre Palestinien·ne·s et Israélien·ne·s ; bell hooks écrit sur l’éducation à/par l’émancipation dans le contexte des discriminations raciales aux États-Unis ; enfin, trois participant·e·s à des groupes de rencontre en Kanaky/Nouvelle-Calédonie nous proposent un troisième point d’ancrage en cette année de référendum d’autodétermination. Un ouvrage collectif qui vise à donner voix ensemble aux militant·e·s et aux théories, engageant un dialogue qui offre un répertoire d’actions et de réflexions puissant et décapant au confluent du féminisme, de l’analyse de la colonialité et d’une radicalité revendiquée. Essais de bell hooks, Rabah Halabi, Michal Zak, Nava Sonnenschein, Ramzi Suleiman, Ahmad Hijazi, Tal Dor, Angélina Perrochaud, Pascal Hébert, Pierre Wélépa et Nassira Hedjerassi.
Postface de Nassira Hedjerassi
Keywords: afrique; amériques; approches et analyses; asie; cours; fem3100; féminisme décolonial; histoire et politique; israël; militance; nouvelle calédonie; océanie; palestine; premier cycle; régions géographiques; thématiques; états-unis

Justice is indivisible: Palestine as a feminist issue - Elia, Nada (Decolonization: Indigeneity, Education & Society, 2017)
⠀⠀⠀⠀⠀⠀⠀⠀⠀
Number: 1
Keywords: approches et analyses; asie; cours; féminisme arabe; féminisme décolonial; histoire et politique; palestine; pol4212; premier cycle; ressource en ligne; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Conférence: «Retour du sacré et politique des différences culturelles» (2012)
Conférence de Haideh Moghissi présentée en anglais le 3 octobre 2012 à l’Institut de recherches et d'études féministes. Haideh Moghissi est professeure de sociologie et d'études des femmes à l'Université York (Toronto). Elle a été fondatrice de l'Union nationale des femmes iraniennes et membre de ses premiers comités exécutif et de rédaction, avant de quitter l'Iran en 1984.
Keywords: approches et analyses; asie; discipline; droits des femmes*; féminisme islamique; histoire et politique; iran; militance; mouvements des femmes*; ressource en ligne; régions géographiques; science politique; science politique et droit; thématiques

Sustainable development, water resources management and women's empowerment: The Wanaraniya water project in Sri Lanka - Aladuwaka S.; Momsen J. (Gender and Development, 2010)
Water is one of the most important natural resources, and its effective management is essential given its scarcity. In rural Sri Lanka, the management of available water resources needs special attention because investment for water resource improvement is hard to obtain, and water itself is relatively scarce in the drier areas of the country. The Wanaraniya Water Project pipes water 6.5km from its source to individual houses in the village, saving women daily time and effort. The project is founded on commitments to community participation and the adoption of local knowledge. It was initiated by women, and has been operated and managed by them for the last six years. This study argues that the project can serve as a model for better planning of water management, and focuses on the unique strategies and innovative methods that have been used. In particular, it shows the impact of involvement in the project on women’s empowerment. The implementation of the project has helped women to improve their leadership qualities, confidence, self-reliance, and gain more power in the community through their successful establishment of a village water supply.
Keywords: approches et analyses; asie; cours; discipline; développement; développement participatif; environnement; géographie; histoire et politique; justice sociale; pol4022; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sri lanka; thématiques; études de genres